ENGLISH LANGUAGE TEACHING AT VARIOUS LEVELS - Abdurahmonova, Zebo (Журнал иностранных языков и лингвистики, 2023)
English has an important role in the world as an international language. English is like a window to the world because by English you can learn about the world and you can get more information from the world. If you want to be a knowledgeable person, English is important to be learned. Having ability in English also will help the students to study because what he or she learned is not limited to the one in their country but also in the world. English has several advantages when it has been taught since in an elementary school, three of which are elementary school age is a brilliant time to learn a second language, preparation English in the junior high school, and preparation to face the globalization era.